MODERASI PENGENDALIAN INTERNAL ATAS PENGARUH DIGITAL ACCOUNTING DAN FORENSIC ACCOUNTING TERHADAP EFEKTIVITAS DETEKSI KECURANGAN PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI DI BEI (2022–2024) - Puji Aledya Angguna; Martinus Budiantara (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze the influence of Digital Accounting and Forensic Accounting on the effectiveness of fraud detection with internal control as a moderating variable in consumer goods manufacturing companies listed on the Indonesia Stock Exchange for the 2022–2024 period. This study uses a quantitative approach with a moderated regression analysis (MRA) method. Research data were obtained from financial statements and annual reports of companies that met the research sample criteria. The independent variables in this study are Digital Accounting and Forensic Accounting, the dependent variable is the effectiveness of fraud detection, while internal control acts as a moderating variable. The results show that Digital Accounting has a positive and significant effect on the effectiveness of fraud detection. Forensic Accounting also has a positive and significant effect on the effectiveness of fraud detection in the basic regression model (main effect). In addition, internal control has been shown to moderate the effect of Digital Accounting on the effectiveness of fraud detection, indicating that a good internal control system can strengthen the use of digital accounting technology in detecting fraud. However, internal control has not been shown to moderate the effect of Forensic Accounting on the effectiveness of fraud detection. This research is expected to contribute to companies in improving fraud detection systems through the application of digital accounting technology, forensic accounting, and strengthening internal controls.